The Effect Of Elderly Exercise On Vo2max Levels In The Elderly Using Fabric Mask And Surgical Mask In Sidodadi Village, Deli Regency, Serdang In The New Normal Era - Timbul Siahaan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
The Covid-19 virus is a virus that attacks the immune system, this causes the spread from human to human to increase. In the process of preventing and slowing the transmission of Covid-19, the WHO (World Health Organization) issued recommendations for social isolation and restrictions on daily behavior, significantly reduced activities with greater energy expenditure, changing physical exercise patterns, increasing healthy lifestyles, environmental disinfection. and use of personal protective equipment such as masks. Research has found that decreased activity can lead to an increased risk of cardiovascular disease, reduce muscle mass and produce significant changes in the metabolism of the immune system, especially in the elderly. Various studies provide evidence that the use of masks can prevent droplets from spreading. The immune system is very responsive to moderate-intensity exercise and the incidence of respiratory tract infections/disorders is lower. Gymnastics/exercise is strongly associated with increased cardiorespiratory fitness such as greater oxygen consumption (VO2max).